“La Aplicación de la Suspensión Condicional de la Pena en las Contravenciones Penales y de Tránsito” - González Roa, Katherine Lizbeth (2021)
This thesis entitled: “THE APPLICATION OF THE CONDITIONAL SUSPENSION OF THE PENALTY IN CRIMINAL AND TRANSIT CONTRAVENTIONS”, refers to the need to allow the Ecuadorian legal system to expand the legal figure of the conditional suspension of the penalty so that it is also a guarantee for both criminal and traffic offenses; It is necessary to specify since said suspension would not be appropriate for all violations, that is, those of violence against women or members of the family nucleus are excepted since it is more valuable to protect the central nucleus of society; nor will it proceed for repeat offenders. Currently, the Ecuadorian penal system neither admits nor prohibits the application of this alternative mechanism when dealing with violations; Although it is true, article 630 of the Código Orgánico Integral Penal regarding the legal figure of the Conditional Suspension of the Penalty allows the sanction that deprives the right to freedom to be suspended for crimes that do not exceed five years, however, in practice it does not constitute a benefit for the primary offender, author of a conduct of little social connotation whose privative sentence causes more damage than benefits since the short time that he will remain in prison is not enough for the offender to fulfill the purpose of comprehensive rehabilitation that he manifests the rehabilitation system regarding every sentenced person, on the contrary, corrupts, degrades, withers the honesty of the person who has entered prison for the first time, which will generally mean being overcrowded and in contact with dangerous behaviors. By not allowing the application of this alternative mechanism in contraventions, the principle of minimum intervention determined in our legal system and endorsed by international human rights instruments is not being revered; thus considering that criminal intervention is legitimized only when it is strictly necessary, being the last resort, which will intervene when the other extra- criminal mechanisms aren ́t sufficient; for the new trends in criminal law, it ́s essential not lo lock 5 up the perpetrator of the conduct in a penitentiary, but to provide an effective solution that guarantees comprehensive reparation and the opportunity for the offender to continue leading a life in your usual environment, so that can continue to generate financial support for their family nucleus without it being affected as well as their working life by a behavior of little incidence, in addition to what it would mean for the State to save resources in terms of prison maintenance expenses. This research was developed based on a conceptual, doctrinal and legal study with national and international regulations, as well as through different methods such as surveys, interviews and case studies, which finally allowed me to propose a reform legal to the Código Orgánico Integral Penal in reason that insert an unnumbered article that allows the application of the conditional suspension of the penalty to criminal and traffic offenses for being misconduct of little social impact.